2011
DOI: 10.1097/ccm.0b013e3182281f1b
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of critically ill patients with acute kidney injury using the Acute Kidney Injury Network criteria*

Abstract: Objective Acute kidney injury (AKI) affects 5–7% of all hospitalized patients with a much higher incidence in the critically ill. The Acute Kidney Injury Network proposed a definition in which serum creatinine rises (>0.3mg/dl) and/or oliguria (<0.5/ml/kg/h) for a period of 6 hours are used to detect AKI. Accurate urine output measurements as well as serum creatinine values from our database were used to detect patients with AKI and calculate their corresponding mortality risk and length of stay. Design Retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
3
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 28 publications
7
97
3
2
Order By: Relevance
“…Hospital LOS was significantly higher in patients with AKI (3 days [IQR, 2-5] versus 10 days [IQR, [6][7][8][9][10][11][12][13][14][15][16]] versus 3 days [IQR, 2-5]; P,0.001), and increased with increasing severity of AKI (n=25,859 patients). In multivariable quantile regression analysis, AKI was associated with a 2.8-day higher LOS and a $7082 increase in costs (P,0.001).…”
Section: Los and Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital LOS was significantly higher in patients with AKI (3 days [IQR, 2-5] versus 10 days [IQR, [6][7][8][9][10][11][12][13][14][15][16]] versus 3 days [IQR, 2-5]; P,0.001), and increased with increasing severity of AKI (n=25,859 patients). In multivariable quantile regression analysis, AKI was associated with a 2.8-day higher LOS and a $7082 increase in costs (P,0.001).…”
Section: Los and Costmentioning
confidence: 99%
“…AKI is strongly associated with increased resource utilization (1-3), higher short-and long-term mortality (1,(4)(5)(6)(7)(8)(9), and a higher risk for the development of CKD (10)(11)(12)(13). Since 2004, at least four proposals have been put forth to define and stage AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Because a prior SCr was not always available for staging AKI recovery patients, the nadir during admission was substituted (20). We excluded patients receiving chronic dialysis for ESRD, organ transplantation, palliative care, transient SCr changes (return to baseline within 24 hours), or erroneous SCr values from spurious blood samples.…”
Section: Patient Populationmentioning
confidence: 99%
“…Our study results are very much similar to other studies from western countries that report an incidence of AKI of 20-50% depending on the criteria used and the patient population studied. 9,12,14,[26][27][28] In our study, incidence of AKI was higher when AKIN criteria was used compared to RIFLE criteria. This is very much expected since AKIN Although several studies from India have reported the epidemiology of AKI, very few studies have systematically explored the epidemiology of AKI in the critically ill population or have used validated criteria, such as RIFLE or AKIN.…”
Section: Discussionmentioning
confidence: 72%